Efficiency of natural mating and artificial insemination in turkey (Meleagris gallopavo) breeding (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
This study was conducted to compare the reproductive and economic performance of turkey hen bred by natural mating (NM) and artificial insemination (AI) using fresh and chilled semen. The breeding trial was designed under a completely randomized design (CRD) consisting of three treatment groups (T1 = NM following ♂1:♀4, T2 = AI with fresh semen and T3= AI with chilled semen). A total of 48 turkey hens and 8 toms were used with 4 replicates in each treatment group. Semen collection was performed by using the abdominal massage technique. Semen aliquots was diluted by modified ringer‟s solution at the ratio of 1:2 and then stored at 3−50C temperature in refrigerator for 24 hours. Undiluted fresh pooled semen was deposited into the vagina @ 0.02 ml/hen within 30 minutes of collection; and pooled diluted chilled semen was deposited @ 0.2 ml/hen at 4−5 pm in every week. Both NM and AI had no significant effect on egg production, egg weight, hatchability and survivability of poults. Significantly (P